LIVER MORPHOMETRIC CHANGES DURING FETAL DEVELOPMENT IN EXPERIMENTAL KIDNEY DISEASE: A COMPARATIVE ANALYSIS - Rakhmankulova N.G. (Central Asian Journal of Medicine, 2025)
For the first time, a systematic investigation was conducted on white fetal rats with experimentally induced chronic kidney disease (CKD) to assess morphological changes in different regions of liver tissue. The study evaluated the effects of Juizar water treatment by analyzing morphometric parameters of the liver to determine its therapeutic efficacy. Additionally, the research aimed to establish early diagnostic criteria for liver cell damage based on experimental findings. The results were used to develop examination protocols for treating women with CKD, with a focus on predicting and preventing liver complications. Further studies were conducted to prepare reproductive age women particularly pregnant women for healthy fetal development by enabling early detection and prevention of liver cell damage. In Uzbekistan, work is carried out to improve the social protection of the population and the quality of medical services. Steps are taken towards the elimination of chronic liver diseases, prevention of their consequences, as well as the introduction of early diagnosis and effective treatment methods. In this regard, it is important to improve the skills of medical personnel, introduce modern diagnostic tools and provide the population with the right health information. In the Prevention of liver diseases, the formation of the right lifestyle and regular medical examinations are central. The reforms carried out in this way in our country serve to improve the quality of prevention and treatment of diseases.